ANALYSIS OF THE EFFECT OF WORK STRESS AND NON PHYSICAL WORK ENVIRONMENT ON JOB SATISFACTION AND ITS IMPACT ON EMPLOYEE TURNOVER INTENTION (Study on employees of PT. MUSTIKA DHARMA JAYA LAMONGAN) - Henny Mahmudah (Jurnal Scientia, 2022)
In a company it is necessary to create a good relationship and atmosphere where this is very influential on employee performance. PT Mustika Dharmajaya has good job satisfaction which is reflected in their satisfaction with both fellow co-workers and with their own work. This study aims to analyze the effect of work stress and non-physical work environment variables on job satisfaction and their impact on employee turnover intention. This research was conducted at PT Mustika Dharma Jaya Lamongan. The number of samples set is 80 respondents with sampling using simple random sampling method. The measurement in the questionnaire uses a Likert scale. The data analysis method used is the Structural Equation Model (SEM) with the help of the AMOS 16.0 program. The results of testing the hypothesis show that the work stress variable has a positive and significant effect on employee turnover intention. Job stress has a positive effect on job satisfaction. Non-physical work environment has a positive effect on job satisfaction. The non-physical work environment has a positive effect on employee turnover intention. Job satisfaction has a positive effect on turnover intention. From the results of the path analysis, it shows that the direct influence of work stress and non-physical work environment on employee turnover intention through job satisfaction is 0.284 and 0.195, respectively.